2008
DOI: 10.1891/1939-2095.1.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner Home-Based Primary Care: A Model for the Care of Frail Elders

Abstract: Growing numbers of frail older adults fi nd it increasingly diffi cult to leave their homes in order to access health care. Primary care providers in the home-based setting must have expertise in chronic illness management, illness and injury prevention, and quality-of-life care. Th e doctor of nursing practice brings specifi c competencies and nursing background to the role of primary care provider and is therefore the ideal health professional to provide primary care to frail elders in this setting. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…Nevertheless, the outcomes of the service showed that it is difficult to operate with only a physician visit and that a nurse visit is also necessary for HBPC for homebound patients. In Japan, nurses provide HBPC services at nursing stations [ 14 ] and in the US HBPC model, nurse’s role is pivotal [ 9 , 33 ]. It is difficult to apply the model of the US to Korea, which does not have nurse practitioners [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the outcomes of the service showed that it is difficult to operate with only a physician visit and that a nurse visit is also necessary for HBPC for homebound patients. In Japan, nurses provide HBPC services at nursing stations [ 14 ] and in the US HBPC model, nurse’s role is pivotal [ 9 , 33 ]. It is difficult to apply the model of the US to Korea, which does not have nurse practitioners [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Providenciar à pessoa uma intervenção de intensidade da dor, nas pessoas em residências para idosos, acompanhadas por enfermeiros (28)(29)(30)31) .…”
Section: Discussionunclassified